INSANǴA MANIPULYACIYALÍQ TÁSIRDIŃ ÓZGESHELIKLERI - Joldasbayev, O.Y. (SCIENCE and SOCIETY, 2024)
This article talks about the definitions given to information and the wide application of the concept of manipulation in the psychological effect of information on a person. Concealment information is analyzed as a mandatory sign of manipulation.